Challenges and barriers to advocacy: A student perspective. Issue 12 (13th June 2018) - Kennedy, Samantha
Abstract : The word "disability" carries multiple definitions across contexts, which are often at odds. While I am disabled according to the Americans with Disabilities Act, I have never considered myself a person with a disability. I was nudged to advocate for myself as a child, even though I was resentful being asked to disclose my disability to strangers, while I was still struggling to accept the label myself.